Pengaruh Budaya Organisasi, Komitmen Organisasi, dan Motivasi Kerja Pegawai Dinas Sosial Kota Kediri - Nisa Ermawati; Diana Ambarwati; Nuril Aulia Munawaroh (PPIMAN Pusat Publikasi Ilmu Manajemen, 2026)
This study aims to determine the influence of organizational culture, organizational commitment, and work motivation on the job satisfaction of Kediri City Social Service employees, both partially and simultaneously. The research method uses a quantitative approach with data collection techniques through questionnaires and interviews. The research sample was determined by purposive sampling method from a population of 52 employees, so that 30 respondents were obtained. Data analysis was carried out through validity tests, reliability tests, classical assumption tests (normality, linearity, multicollinearity, and heteroscedasticity), multiple linear regression, determination coefficient (R²), and t-test and F test with the help of SPSS software version 25. The results of the study show that partially organizational culture, organizational commitment, and work motivation each have a significant effect on employee job satisfaction. Simultaneously, these three variables were also shown to have a significant effect on job satisfaction with a contribution of 74.7%, while the remaining 25.3% were influenced by other factors outside this study. These findings affirm the importance of strengthening organizational culture, increasing commitment, and work motivation as a human resource management strategy to increase employee job satisfaction, thereby supporting the effectiveness of organizational performance.